Comparison of the Effects of Digoxin and Bevacizumab on Oxygen-Induced Retinopathy Rat Model - Balbaba, Mehmet; Guler, Seda Duran; Ulas, Fatih; Canleblebici, Mehmet; Yıldırım, Hakan; İncili, Canan Akdeniz (Gazi Eye Foundation, 2023)
Purpose: To evaluate the effect of digoxin on oxygen-induced retinopathy (OIR) model and compare the results with bevacizumab treatment. Methods: Twenty-eight newborn Sprague-Dawley rats were randomly divided into four groups:control group, normoxia+intraperitoneal (ip) normal saline (NS); OIR group, OIR+ip NS; OIR+digoxin group, OIR+ip 0.1 mg/kg of digoxin; and OIR+bevacizumab group, OIR+ip 2.5 mg/kg of bevacizumab. The rats were exposed to 50% oxygen for 24 h, followed by 10% oxygen for 24 h, to induce OIR. This cycle was repeated seven times until 14 days postnatal (P). In all groups, single-dose injections were administered on P15th day. Histopathological and immunohistochemical examinations were performed at the end of the study. Results: The mean neovascular cell nuclei counts (NVCN) of the four groups were 9.00±3.16, 41.80±11.44, 19.38±2.20, and 16.00±2.62. The mean NVCN count was significantly reduced in the treatment groups compared to the OIR group (p<0.001). The mean NVCN count was similar between the treatment groups (p=0.078). In immunohistochemical staining, the immunoreactivity values of the vascular endothelial growth factor (VEGF) were 0.01±0.00, 1.65±0.30, 0.09±0.08, and 0.04±0.02, and the tumor necrosis factor alpha (TNF-?) values were 0.10±0.00, 1.12±0.18, 0.18±0.13, and 0.14±0.05. In the OIR group, VEGF and TNF-? immunoreactivity increased markedly compared to the control group (p<0.001). VEGF and TNF-? immunoreactivity of the treatment groups decreased significantly compared to the OIR group (p<0.001). VEGF and TNF-? immunoreactivity were similar between the treatment groups (VEGF:p=0.752; TNF-?:p=0.099). Conclusions: Retinal neovascularization was significantly suppressed by digoxin treatment, and this effect was comparable to bevacizumab in the OIR model. © 2023 Gazi Eye Foundation. All rights reserved.
Keywords: bevacizumab; digoxin; oxygen-induced retinopathy; tumor necrosis factor-?; vascular endothelial growth factor